Area-Based Compassionate Communities: A systematic integrative review of existing initiatives worldwide. (March 2022) - Quintiens, Bert; D'Eer, Louise; Deliens, Luc; Van den Block, Lieve; Chambaere, Kenneth; De Donder, Liesbeth; Cohen, Joachim; Smets, Tinne
Background: Area-Based Compassionate Communities are community public health interventions which focus on the role of the community in palliative care provision. They apply a set of actions based on the Ottawa Charter for Health Promotion which aims to increase people's control over their health. Aim: To review and compare Area-Based Compassionate Communities with respect to their contextual characteristics, development processes and evaluations. Design: A systematic integrative review with narrative synthesis. Registered in Prospero: CRD42020173406. Data sources: Five databases (Pubmed, Web of Science, PsycInfo, Embase and Scopus) were consulted, consisting of publications from 1999 onwards. This was supplemented with grey literature and author-provided documentation. Results: Twenty articles were drawn from the peer reviewed search, three from grey literature and two from author-provided documentation. Notwithstanding the substantial variation in what is reported, all Area-Based Compassionate Community initiatives focus on multiple action areas of the Ottawa Charter for Health Promotion. Variability in their contextual and developmental characteristics is high. Only a minority of initiatives have been evaluated and although conclusions are generally positive, what is evaluated often does not match their aims. Attaining support from policy makers can help in obtaining funding early in the project. Strengthening people's social networks was a recurring community engagement strategy. Conclusions: While the concept of Area-Based Compassionate Communities is gaining momentum as a new paradigm for the creation of palliative care capacity across society, only a handful of initiatives have been described. The lack of formal evaluations of their envisaged health benefits indicates a pressing need for rigorous research about ongoing and future initiatives.